Innovating For The Future: A Critical Analysis of Curriculum Development Models KBK, KBM, KTSP, K13, and Merdeka Curriculum - Agus Setiawan; Shofi Syifa’ul Fuadiyah Ahla (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
This article aims to concept of the curriculum is its form, independence in thinking has been determined by educators with the meaning that the main spearhead is educators in helping success in education. This study aims to describe the concept of the KBK, KBM, KTSP, K13, and Merdeka curriculum innovation models. This type of research is a literature review, using journal articles that have been collected from the period 2018-2022. Based on the journal articles that have been used, the following results are obtained: (a) Focusing on the community, with learning resources using textbooks or the community itself. Being disciplined in class is a shared obligation not based on coercion. The main point of the teaching method is to solve problems in order to meet the various needs of all parties. Major schemes for learning include field trips, as well as resource persons from the community survey. (b) the innovative parts of KTSP include the application of life skills learning, as well as self-development in terms of characteristics and other needs. (c) Study preparation is an important part of learning administration including syllabus and lesson plans. After completing the preparation of lesson plans, move on to the implementation of learning that focuses on 3 points, namely: a scientific approach where the learning process is carried out in the classroom, assessment based on plans and case-based studies. The assessment used in the 2013 curriculum is authentic assessment, various types of test models such as observation, portfolio; (d) The main policy is the implementation of national assessments, competencies and character surveys, in which the assessment emphasizes student literacy and numeracy. Second, assessment facilities based on the internet of things, augmented reality and the use of artificial intelligence in assessment.